2012
DOI: 10.1093/cvr/cvs258
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-204 regulates vascular smooth muscle cell calcification in vitro and in vivo

Abstract: Our study has shown that down-regulation of miR-204 may contribute to β-glycerophosphate-induced VSMC calcification through regulating Runx2. miR-204 represents an important new regulator of VSMC calcification and a potential therapeutic target in medial artery calcification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
141
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(149 citation statements)
references
References 39 publications
7
141
0
1
Order By: Relevance
“…59 Interestingly, it was shown that RUNX2 is one of the most conserved predicted targets of miR-204 60 and is regulated by this miRNA in systemic vascular disease. 61 As expected, we documented that in vitro downregulation of miR-204 in healthy PASMCs results in RUNX2 and HIF-1α activation, while miR-204 upregulation in PAH-PASMC results in decreased RUNX2 and HIF-1α activation. 56,59 These effects are associated with decreases in both PASMC proliferation and apoptosis resistance in PAH.…”
Section: Molecular Contribution Of Pasmcs To Pah Phenotypesupporting
confidence: 85%
“…59 Interestingly, it was shown that RUNX2 is one of the most conserved predicted targets of miR-204 60 and is regulated by this miRNA in systemic vascular disease. 61 As expected, we documented that in vitro downregulation of miR-204 in healthy PASMCs results in RUNX2 and HIF-1α activation, while miR-204 upregulation in PAH-PASMC results in decreased RUNX2 and HIF-1α activation. 56,59 These effects are associated with decreases in both PASMC proliferation and apoptosis resistance in PAH.…”
Section: Molecular Contribution Of Pasmcs To Pah Phenotypesupporting
confidence: 85%
“…To test the effect of miR-204 in vivo, mice were treated with vitamin D 3 to induce calcification and simultaneously with a miR-204 agomir (miRNA mimic). In these mice, Runx2 was not upregulated and aortic calcification was similar to controls (16). Similarly, miRNA-30b and miRNA-30c (which target and downregulate Runx2) were shown to be downregulated by bone morphoge- netic protein-2 (BMP-2), and the loss or knockdown of these miRNAs in vivo increased Runx2 expression and calcification (6).…”
Section: Emerging Concepts In Vascular Calcificationmentioning
confidence: 78%
“…However, we now have the means to study calcification in AVS using human tissues [14,15,29], which according to our results, may be the only effective way to study the disease. Our study is limited, however, in that it only explores ALP-dependent calcification and does not address other molecular contributors including Runx2 [30], Wnts [4], UII [15], BMPs [31], and TGF-β [32]. Furthermore, we cultured our cells in OSM for 7 days for HAVICs and 12 days for BAVICs, while other studies assess calcification onset after much longer incubation times [33].…”
Section: Discussionmentioning
confidence: 99%